Violence and discrimination against trans women in Perú and the fundamental rights to health, housing and work - Ramírez Bernal, Víctor Raúl Jesús (2024)
The objective of the research is to demonstrate that, in Peru, the lack of recognition of gender identity in the National Identity Document (DNI) of transsexual women generates abuse and discrimination, in addition to violating their right to health and safety job. The present investigation addresses the problem that the Peruvian State refuses to recognize transsexual women regarding their gender identity. The normative and theoretical basis that supports the mistreatment and discrimination of transsexual women will be developed, as well as the analysis of the lack of health and work. The methodology applied in this research was based on the analysis of legal and jurisprudential documents, both national and international. The result of this research is to identify if there are problems regarding the right to health and work that affect transsexual women. The conclusion is that, in our Peruvian society, there is a heteronormative ideology that leads to rejection and limits the enrichment of our legal system, compared to other countries. It is recommended to implement procedures in the legal and administrative area of the Peruvian State, corresponding to processing, with greater speed and efficiency, the request for gender change in the DNI.